2007
DOI: 10.1063/1.2717174
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the effects of orientation and corrugation for H2 adsorbed on polycyclic aromatic hydrocarbons

Abstract: This paper reports state-of-the-art ab initio calculations at the second order of Moller-Plesset perturbation theory of molecular hydrogen interaction with polycyclic aromatic hydrocarbons (PAHs) up to coronene (C(24)H(12)). The effects of both H(2) orientation with respect to the PAH plane and of PAH corrugation have been carefully investigated. It was found that the energetic preference for the perpendicular H(2) orientation over the parallel one decreases rapidly as the PAH grows. The detailed study of coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…This value differs substantially from the MP2 bond length of 0.767 , and compares well with the experimental value of 0.7414 . Thus, the difference between the reported MP2/CBS binding energy of 5.13 kJ mol À1 for the most stable configuration (B1z) and the corresponding value of Donchev [4] (5.32 kJ mol…”
Section: à8mentioning
confidence: 91%
See 4 more Smart Citations
“…This value differs substantially from the MP2 bond length of 0.767 , and compares well with the experimental value of 0.7414 . Thus, the difference between the reported MP2/CBS binding energy of 5.13 kJ mol À1 for the most stable configuration (B1z) and the corresponding value of Donchev [4] (5.32 kJ mol…”
Section: à8mentioning
confidence: 91%
“…Recently, large discrepancies between the previously published MP2/AVQZ results for the benzene···H 2 complex have been reported. [4] The detailed analysis revealed that these discrepancies stem mainly from the choice of the HÀH internuclear separation. Herein, we have aimed at the CCSD(T)/CBS description of hydrogen interactions with various graphitic surfaces and therefore have used a CCSD(T)/ AVQZ internuclear separation of 0.742 .…”
Section: à8mentioning
confidence: 98%
See 3 more Smart Citations